Didactic Views of Abdulla Avloni (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this school, without knowing how the development of the practice of the “Young Generation” and the theory of Ukichichi took place, it is impossible to scientifically solve the issues of educating young people as perfect people in all respects. To successfully resolve the issue of raising morally pure and mature people, it is very important to study historical traditions, spiritual wealth, scientific heritage and historical and educational experience of our ancestors, and to apply ix achievements in life and education.